PENGOMPOSAN K1UDGE HASIL PENGOLAHAN LIMBAH CAIR PT. INDOFOOD CBP DENGAN PENAMBAHAN LUMPUR AKTIF DAN EM4 DENGAN VARIASI SAMPAH DOMESTIK DAN KULIT BAWANG - Bening Laksa Intan; Syafrudin Syafrudin; Winardi Dwi Nugraha (Jurnal Teknik Lingkungan, 2013)
Sludge from food industry potentially treated with composting methods because of any organic matter such as carbohydrates, ptoteins, fat, coarse fiber, water and macro nutrient such as nitrogen and phosphorus. This research will be conducted composting process that Sludge mixed with domestic wastes and onion skins. Composting process used two activators. They are Effective Microorganism 4(EM4) and aktivator  from activated Sludge. Compost matured have meet the requirerements of SNI 19-7030-2004. The best result at variations on activator EM4 with ratio K1udge : domestic wastes : onion skins = 6:1:1 eith result C-organic 13,56%,N-total 0,91%, P-total  0,5%, K-total 0,53% and the C/N ratio 14,37. In the activator of activated K1udge with same variation show result C-organic 12,62%,N-total 0,67%, P-total  0,42%, K-total 0,5% and the C/N ratio 18,98.